2017
DOI: 10.1111/ipd.12308
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between jaw‐muscle activity measurement with portable single‐channel electromyography and polysomnography in children

Abstract: Background Polysomnography (PSG) is the gold standard for sleep bruxism (SB) assessment. High economical costs, complex technical equipment, and unfamiliar laboratory setting limit its use in children. Aim To determine the night‐to‐night variability of electromyography (EMG) episodes during a five‐night recording with the GrindCare Measure (GCM), and the agreement in the assessment of masticatory muscle activity (MMA) between GCM and PSG in children. Design Forty‐seven children from clinics of Universidad CES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…1). As others have also concluded [7,18,20], it seems that setups based exclusively on EMG provide a poor indication of the true MMA activity. There is a significant risk for MMA event overscoring with EMG-only setups, as OFA or OMA events could not be recognized reliably (Figs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1). As others have also concluded [7,18,20], it seems that setups based exclusively on EMG provide a poor indication of the true MMA activity. There is a significant risk for MMA event overscoring with EMG-only setups, as OFA or OMA events could not be recognized reliably (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…Carra et al compared the PSG with and without audio and video recordings and found a 24% overestimation in the MMA index when no audio or video footage was used in scoring [12]. Several studies have reported varying agreement levels between setups that use only EMG compared to PSG-AV [7,19,20]. Our group has previously compared a forehead electrode set (FES) recording for PSG-AV and found that the MMA event indices recorded fully with FES correlated well with the values obtained with PSG-AV [21].…”
Section: Introductionmentioning
confidence: 99%
“…This study used sEMG recorded MMA because it was considered to be a safe, non‐invasive, reproducible and a simple‐to‐analyse method used in children in many studies . PMCs have been subject to occlusal studies based on models, clinical photos, clinical measurements, electronic occlusal sensor devices and occlusal bite force devices .…”
Section: Discussionmentioning
confidence: 99%
“…10 The criteria cannot simply be "copied and pasted" without validation in different age populations: children, adolescents, and adults. [11][12][13][14] In the dental field, SB was considered as a parafunction, an activity occurring in parallel to masticatory function. A very recent consensus, updating the one published in 2013, suggested that "sleep and awake bruxism are masticatory muscle activities…in otherwise healthy individuals, bruxism should not be considered as a disorder, but rather as a behaviour…" and "bruxism-related masticatory muscle activities should be assessed in the behaviour's continuum."…”
Section: Sleep Bruxism Differs Between Sleep Medicine and Dentistry: mentioning
confidence: 99%